2010 International Conference on Machine Vision and Human-Machine Interface 2010
DOI: 10.1109/mvhi.2010.147
|View full text |Cite
|
Sign up to set email alerts
|

WSN Cluster Head Selection Algorithm Based on Neural Network

Abstract: As an effective way to control the network topology, the clustering algorithm can significantly reduce the energy consumption of wireless sensor networks and improve network throughput. Through learning the framework of clustering algorithm for wireless sensor networks, this paper presents a weighted average of cluster head selection algorithm based on BP neural network which make node weights directly related to the decision-making predictions. The weight distribution of nodes is objective. The simulation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…After reviewing the existing mechanism of clustering optimization, the following are the open‐end research problems identified: Adoption of iterative approach: Majority of the existing mechanism have used iterative mechanism towards performing clustering operation. Multiple rounds of similar operation are carried out in recursive order for finding the best cluster head is witnessed.…”
Section: Research Problemmentioning
confidence: 99%
“…After reviewing the existing mechanism of clustering optimization, the following are the open‐end research problems identified: Adoption of iterative approach: Majority of the existing mechanism have used iterative mechanism towards performing clustering operation. Multiple rounds of similar operation are carried out in recursive order for finding the best cluster head is witnessed.…”
Section: Research Problemmentioning
confidence: 99%
“…Our proposed algorithm is a centralized cluster based protocol strongly related to LEACH-Centralized (LEACH-C) (Guo et al, 2010) and LEA2C (Enami et al, 2010) protocols. The operation of the algorithm is divided into rounds in a similar way to LEACH-C. Each round begins with a cluster setup phase, in which cluster organization takes place, followed by a data transmission phase, in which data from the simple nodes are transferred to the cluster heads.…”
Section: Algorithm Assumptionsmentioning
confidence: 99%
“…Certainly after each data transmission phase, the next cluster head will be a different node (cluster head rotation). After determining cluster head nodes, BS assign appropriate roles to all nodes by sending messages containing related cluster head ID as in LEACH-C (Guo et al, 2010).…”
Section: Three Criteriamentioning
confidence: 99%
“…The clustered approach is considered a more sustainable option [20] and has already been widely adopted for the organization of WSNs because of its advantages over non-clustered, centralized schemes in terms of reliability, robustness, scalability, network lifetime, and so forth [61][62][63][64][65][66]. With clustering, the network is segregated into several clusters that consist of subsets of nodes, establishing a hierarchical structure.…”
Section: Cooperation Architecturesmentioning
confidence: 99%